The application of BIM (Building Information Modelling) with disruptive innovation - Morales-Conejo, Leonardo (2021)
BIM (Building Information Modelling) work method’s primary function is to manage information of a given project or assent, using a graphical interface enriched with additional information and documentation.  The aim of this article is to review some of the disruptive innovations, such as IoT, Big Data, Augmented Reality, Virtual Reality, Blockchain and their potential to complement BIM; thus generating even more powerful dynamic tools to the end user.  This article is based on several undergraduate thesis and publications related to the subject.  This article concludes that combining BIM with IoT allows the creation of digital twins, the application of Big Data helps to manage information from different sources, and how augmented and virtual reality can illustrate the end result of a building project even before its construction ever starts.  Each of these individual innovations provides better management of information on their own, and the combination of these with BIM can open new dimensions in data management.